Autophagic Cell Death Is Induced by Acetone and Ethyl Acetate Extracts fromEupatorium odoratum InVitro : Effects onMCF-7 and Vero Cell Lines - Harun, Faizah; Syed Sahil Jamalullail, Syed Mohsin; Khoo, Boon Yin; Othman, Zulkhairi; Tilwari, Anita; Balaram, Prabha (Hindawi Publishing Corporation, 2012)
Eupatorium odoratum (EO) contains many biologically active compounds, the anticancer effects of which are not well documented. This study evaluates the cytotoxic effects and mechanism of action of EO extracts on MCF-7 and Vero cell lines. Evaluation of the cytotoxic activity using MTT assay, morphological alterations, and apoptosis were carried out. Autophagy was evaluated by LC3-A protein expression. Cytotoxic activity,membrane blebbing and ballooning at 24 hours, replacement bymass vacuolation, and double membrane vesicles mimicking autophagy and cell death were observed in the cancer cells. No apoptosis was observed by DNA fragmentation assay. Overexpression of LC3-A protein indicated autophagic cell death. Cell cycle analysis showed G0 and G2/M arrest. The Vero cells did not show significant cell death at concentrations <100 μg/mL. These results thus suggest that acetone and ethyl acetate extracts of EO induce cell death through induction of autophagy and hold potential for development as potential anticancer drugs.